Do ski jumpers still need to be light? - Virmavirta, M.; Kivekäs, J. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
In ski jumping low body weight development resulted in some serious underweight Problems in the early 2000`s (e.g. Müller 2009a, 2009b). This was most likely a result of a better understanding of the effect of low body weight together with the contemporary suit development on the final performance. The computer simulations (e.g. Schmölzer & Müller 2002) have shown that the jump length markedly increases with decreasing weight. Schmölzer & Müller (2002) mentioned that regulations that compensate heavier athlete`s ballistic disadvantages are needed. The authors added that many suggestions may be valid from the standpoint of physics and their suitability for use should be assessed prior to propose any changes to current regulations. In 2004, Federation Internationale de Ski (FIS) decided to solve the underweight problem by relating maximum ski length to jumpers` body mass index (BMI). The BMI regulation adopted by the FIS (International Ski Federation) was intended to reduce the advantage of being light in ski jumping. Figure 1 shows the development of ski jumpers` average BMI before and right afterthe regulation was introduced. The FIS cut-off point of BMI was originally set to match WHO (1995) underweight value 18.5 kg/m2 (17.0-18.49 kg/m2 mild thinness). Thereafter the cut-off point has been changed a couple of times because of unwanted results in jumpers' body composition. In 2019, the FIS cut-off point of BMI is 21.0 kg/m2 measured with suit (without jumping shoes since summer 2018) corresponding to the correctly measured BMI of 20.5 kg/m2. By adopting the BMI regulation to specifications for competition equipment, FIS succeeded in stopping the alarming development of underweight problems in ski jumping. However, this regulation has not, as expected, totally eliminated the importance of body weight in ski jumping. Therefore, the present study examined the current relationship between body weight, ski length and performance (jumping distance) in ski jumping.